Peran Pemerintah Daerah dalam Pencegahan dan Penanggulangan HIV-AIDS di Kabupaten Merauke - Muh. Rum Ramadhan Rakhman (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2017)
The objectives of this research are to know the efforts made by the government in the municipality to address the prevention and prevention of HIV-AIDS. The type of research used is descriptive qualitative. Technique of collecting data using observation, that is collecting data by conducting direct observation to the object under study, conducting interviews with informants to get as much information as possible by asking some questions about the problems studied and research library by collecting data through written documents, books , Reports, and legislation which is closely related to this research and supported by secondary data. The result of this research shows: First, the District Government of Merauke has made efforts in the prevention and control of HIV-AIDS. Efforts in prevention include improving communication, information and education on HIV-AIDS, increasing condom use, improving the prevalence of sexually transmitted infections, increasing prevention of mother-to-child HIV transmission and raising universal precautions. Efforts in the field of prevention of VCT services, and treatment of people living with HIV. Second, in the implementation of these efforts there are obstacles and challenges. Barriers that occur include low levels of education, still lack of awareness and understanding of the community about the dangers of HIV AIDS and the still stigma and discrimination of HIV-AIDS. The challenges of district government Merauke include the mutation of employees in government institutions, the development of information and communication technology, and population mobility